2019
DOI: 10.3928/23258160-20190503-07
|View full text |Cite
|
Sign up to set email alerts
|

Choriocapillaris Flow Density Negatively Correlates With Advancing Age on Spectral-Domain Optical Coherence Tomography Angiography

Abstract: BACKGROUND AND OBJECTIVE: To correlate subfoveal choriocapillaris (CC) flow density with age using spectral-domain optical coherence tomography angiography (SD-OCTA). PATIENTS AND METHODS: One hundred eighty-three eyes of 94 subjects (66 female, 28 male) were enrolled. Included were healthy subjects between the ages of 21 and 82 years without any history of vitreoretinal disease. Measurements were obtained with software from the OCT devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In our study, we evaluated the CFD of contralateral eyes of nAMD and PCV with OCTA, and found nAMD-contralateral eyes had significantly lower CFD compared with PCV and control eyes, while the difference wasn't statistically significant between PCV group and control. Although CFD was found negatively correlates with aging (17), it is unlikely that aging itself can account for the difference, since PCV and AMD group were age-matched. Another important factor is the existence of drusen, which is considered a hallmark of dry AMD.…”
Section: Discussionmentioning
confidence: 87%
“…In our study, we evaluated the CFD of contralateral eyes of nAMD and PCV with OCTA, and found nAMD-contralateral eyes had significantly lower CFD compared with PCV and control eyes, while the difference wasn't statistically significant between PCV group and control. Although CFD was found negatively correlates with aging (17), it is unlikely that aging itself can account for the difference, since PCV and AMD group were age-matched. Another important factor is the existence of drusen, which is considered a hallmark of dry AMD.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, we evaluated the CFD of fellow eyes of nAMD and PCV groups using OCTA and found that fellow eyes of the nAMD group had significantly lower CFD compared with the PCV and control group, and the differences between the PCV group and the control group or between PCV subtypes were not statistically significant. Although CFD was found to be negatively correlated with aging [19], it is unlikely that aging itself can account for the difference because the PCV, AMD, and control group were age-matched. Another important factor is the existence of drusen, which is considered a hallmark of dry AMD.…”
Section: Discussionmentioning
confidence: 94%
“…Spacings of 5 to 20 mm in methacrylate casts of human posterior pole were reported by Olver 57 without individual values or methodologic details. Lengths of choriocapillaris lumens were incorporated only into vascular density, an aggregate measure, by Ramrattan et al 17 Reduced flow signal density, analogous to vessel density, and increased signal voids (reciprocal of vessel density) have been reported in normal aging, 58,59 early AMD, 60,61 and advanced AMD. 62e64 Published values vary widely (40%e>90% for vascular density) 65e67 and often are higher than histologic measures.…”
Section: Discussionmentioning
confidence: 99%